High-temperature failure of steel boiler tube secondary superheater in a power plant - Sulthoni Akbar; Desrilia Nursyifaulkhair; Leanddas Nurdiwijayanto; Alfian Noviyanto; Nurul Taufiqu Rochman (Universitas Mercu Buana, 2023)
This work investigated the failure analysis of the boiler tube secondary superheats in a power plant utility. The tube was composed of low carbon steel with 2.25Cr-1Mo addition, which was ruptured after a 26 h working test. The investigation of the tube’s failure was performed through several analysis, such as microstructure, elemental analysis, and mechanical test. It was found the abrupt increase in the operating temperature as the primary factor of the material degradation of the tube. The microstructure analysis shows the existence of elongated grain with the formation of microcracks on the grain boundaries, indicating the exceeded stress applied in the material. The hoop stress in the ruptured tube was 42.47 MPa, which is higher than the allowable stress of 23.5 MPa at 605 °C. Furthermore, the equiaxed grain was observed in the unruptured tube, implying the microstructural change after exposure at high temperatures.